Allelic expression of AhNSP2-B07 due to parent of origin affects peanut nodulation - Zhao, Zifan; Wang, Yichun; Peng, Ze; Luo, Ziliang; Zhao, Meixia; Wang, Jianping (Frontiers in Plant Science, 2023)
Legumes are well-known for establishing a symbiotic relationship with rhizobia in root nodules to fix nitrogen from the atmosphere. The nodulation signaling pathway 2 (NSP2) gene plays a critical role in the symbiotic signaling pathway. In cultivated peanut, an allotetraploid (2n = 4x = 40, AABB) legume crop, natural polymorphisms in a pair of NSP2 homoeologs (Na and Nb) located on chromosomes A08 and B07, respectively, can cause loss of nodulation. Interestingly, some heterozygous (NBnb) progeny produced nodules, while some others do not, suggesting non-Mendelian inheritance in the segregating population at the Nb locus. In this study, we investigated the non-Mendelian inheritance at the NB locus. Selfing populations were developed to validate the genotypical and phenotypical segregating ratios. Allelic expression was detected in roots, ovaries, and pollens of heterozygous plants. Bisulfite PCR and sequencing of the Nb gene in gametic tissue were performed to detect the DNA methylation variations of this gene in different gametic tissues. The results showed that only one allele at the Nb locus expressed in peanut roots during symbiosis. In the heterozygous (Nbnb) plants, if dominant allele expressed, the plants produced nodules, if recessive allele expressed, then no nodules were produced. qRT-PCR experiments revealed that the expression of Nb gene in the ovary was extremely low, about seven times lower than that in pollen, regardless of genotypes or phenotypes of the plants at this locus. The results indicated that Nb gene expression in peanut depends on the parent of origin and is imprinted in female gametes. However, no significant differences of DNA methylation level were detected between these two gametic tissues by bisulfite PCR and sequencing. The results suggested that the remarkable low expression of Nb in female gametes may not be caused by DNA methylation. This study provided a unique genetic basis of a key gene involved in peanut symbiosis, which could facilitate understanding the regulation of gene expression in symbiosis in polyploid legumes.